Novel DNA nanoflower biosensing technologies towards next-generation molecular diagnostics. Issue 5 (May 2023) - Sheng, Jing; Pi, Yan; Zhao, Shuang; Wang, Binpan; Chen, Ming; Chang, Kai
Abstract : DNA nanoflowers (DNFs) are topological flower-like nanostructures based on ultralong-strand DNA and inorganic metal-ion frameworks. Because of their programmability, biocompatibility, and controllable assembly size for specific responses to molecular recognition stimuli, DNFs are powerful biosensing tools for detecting biomolecules. Here, we review the current state of DNF-based biosensing strategies for in vivo and in vitro detection, with a view of how the field has evolved towards molecular diagnostics. We also provide a detailed classification of DNF-based biosensing strategies and propose their future utility. Particularly as transduction elements, DNFs can accelerate biosensing engineering by signal amplification. Finally, we discuss the key challenges and further prospects of DNF-based biosensing technologies in developing applications of a broader scope. Highlights: DNA nanoflower (DNF)-based biosensors can efficiently translate information from targeted biomarkers into physical or chemical signals by the unique programmability and massive repeating copies of flower-like structures. DNF biosensing technologies can be designable platforms for both in vitro detection, applied to cells, proteins, small molecules, and in vivo detection, applied to RNA and ATP. DNF-based biosensing technologies present high specificity, sensitivity, biocompatibility, multiplex detection, and point-of-care testing with fast and equipment-free performance. Theranostic flower-like structures can be used as molecular switches to respond to specific intracellular environment and biomarkers, trigger structure degradation, and controllably release particular loadings.